PATTERN OF MALARIAL INFECTION DIAGNOSED AT AYUB TEACHING HOSPITAL ABBOTTABAD - Idris, Muhammad; Sarwar, Javed; Fareed, Jamila (Journal of Ayub Medical College Abbottabad, 2007)
Background: Malaria is endemic in Abbottabad and the adjoining areas like many other parts of the country. Depending upon the environmental conditions different species of malarial parasite are found in different areas. The present study was planned to see the pattern of malarial infection diagnosed at Ayub Teaching Hospital, Abbottabad. Methods: Giemsa stained thick and thin blood films of indoor and outdoor febrile patients sent to the laboratory of Ayub Teaching Hospital Abbottabad with a suspicion of malaria, were examined. Thick film was examined for the diagnosis of malaria while thin films were seen to know the species. Results: Out of 1994 patients screened, 145 (7.2%) were found infected. Plasmodium vivax was seen in the majority (72.47.2%). Plasmodium falciparum was the second common species detected in 24.1 % cases. Mixed infection was seen in 3.44% cases while Plasmodium malariae and ovale was not seen in any patient. Conclusion: Plasmodium vivax was the commonest type of malaria diagnosed at Ayub Teaching Hospital, Abbottabad, during 2002- 2004. Key words: Malaria; Plasmodium